Lope Massaguer and Francisco Batiste: two visions of Mauthausen - Lázaro, Esther (Hispania Nova, 2019)
Lope Massaguer and Francisco Batiste have in common a humble and worker origin, their participation in the civil war, the beginning of their exile in the French camps, their enlistment in the CTE, and their arrival to Mauthausen, as well as their transfer to Ebensee after, his release, and the rest of their life in France. Also joins them that both waited at the end of their lives to write their memories of the experiences lived in the camp. The comparison of both testimonies (Massaguer’s Mauthausen: fin de trayecto and Batiste’s El sol se extinguió en Mauthausen) and, therefore, their vision of Mauthausen, is what is presented in this paper.of those from a comparative approach.